The Role of The Nation and Political Union (Kesbangpol) DKI Jakarta in Doing Community Organization Development - Sabena Sabena; Syerli Hayati; Taufan Bakri (Journal of Islamic Economics and Social Science (JIESS), 2022)
The  number  of  community  organizations  that  have  sprung  up  in  the  DKI Jakarta area and its surroundings continues to grow and requires serious attention from the government and the public, considering that the existence of these organizations is feared to be incompatible with its true function, as a link to convey input to the government, related parties from the voice of the community. Ormas as the front line in knowing the problems around them, the role of mass organizations in a picture of life that occurs in society, if left alone  without  supervision  and  guidance  is  not  impossible  for  mass organizations to become a tool of political propaganda and become a weapon to create conflict in society, because this For this reason, it is necessary to provide guidance to all community organizations so that they return to their functions  as  government  control,  the  chain  of  messengers,  information  on phenomena  that  occur  in  the  midst  of  society,  providing  input  from  all elements of society. In this case, the national and political unitary body plays a  role  in  providing  guidance  to  mass  organizations,  starting  from  the establishment  permit  letter,  determining  the  activity  permit  decision  letter and knowing who is the administrator. Monitoring activities continue to be carried  out  by  synergizing  programs  that  can  directly  involve  the  mass organizations. Part of the coaching is expected to be able to control the mass organizations so that they do not become wild and misfunction.